2021
DOI: 10.1159/000517281
|View full text |Cite
|
Sign up to set email alerts
|

Association between Net Ultrafiltration Rate and Renal Recovery among Critically Ill Adults with Acute Kidney Injury Receiving Continuous Renal Replacement Therapy: An Observational Cohort Study

Abstract: <b><i>Introduction:</i></b> Higher net ultrafiltration (UF<sub>NET</sub>) rates are associated with mortality among critically ill patients with acute kidney injury (AKI) and treated with continuous renal replacement therapy (CRRT). <b><i>Objective:</i></b> The aim of the study was to discover whether UF<sub>NET</sub> rates are associated with renal recovery and independence from renal replacement therapy (RRT). <b><i>Methods:&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Ultrafiltration may be an intuitive approach to addressing AKI-associated delirium, due to fluid overload; however, any potential benefits of ultrafiltration need to be balanced with the concerns related to cerebral hypoperfusion [ 95 ] and worsened renal recovery [ 96 ]. Although delirium has not been specifically evaluated in prior studies using ultrafiltration, prior studies have shown improved rates of extracerebral organ dysfunction with lower compared to higher rates of ultrafiltration [ 96 ]. Future studies are needed to examine the viability of ultrafiltration in hypervolemic patients with AKI to mitigate delirium.…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…Ultrafiltration may be an intuitive approach to addressing AKI-associated delirium, due to fluid overload; however, any potential benefits of ultrafiltration need to be balanced with the concerns related to cerebral hypoperfusion [ 95 ] and worsened renal recovery [ 96 ]. Although delirium has not been specifically evaluated in prior studies using ultrafiltration, prior studies have shown improved rates of extracerebral organ dysfunction with lower compared to higher rates of ultrafiltration [ 96 ]. Future studies are needed to examine the viability of ultrafiltration in hypervolemic patients with AKI to mitigate delirium.…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…Murugan et al undertook two studies on the same cohort of critically ill AKI-D patients treated with CRRT in Australia and New Zealand (n = 1433) to determine the association between net UF rate and time to renal recovery [ 18 , 19 ]. The studies showed that higher net UF (>1.75 mL/kg/hour) correlated with more time to renal recovery and lower incidence of patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Modifiable factors that may play a role in predicting and hence promoting better care of AKI-D include the dialysis prescription and the dialysis procedure in the outpatient setting. However, most studies assessing the role of dialysis prescriptions on AKI-D patient outcomes have been conducted in the inpatient setting [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, another study revealed an association between higher net ultrafiltration and improved survival rate ( 32 ). Similarly, the association between net ultrafiltration rate and renal recovery rate has yet to be established ( 33 ). Other factors, such as fluid overload status and input fluid volumes, may influence clinical outcomes and should also be carefully considered ( 34 ).…”
Section: Discussionmentioning
confidence: 99%